Cơ chế hình thành động đất sóng thần cực đại trong đới hút chìm Manila, Philippin - Lương, Nguyễn Văn; Dương, Nguyễn Văn (Vietnam Journal of Earth Sciences, 2008)
A model of the largest tsunamigenic earthquake generation in Manila subduction zone